Hubungan dukungan sosial dan ketaatan pengobatan dengan kekambuhan pasien skizofrenia di Rumah Sakit Tjitrowardojo Kabupaten Purworejo - Eti Setiati; Sumarni DW; Sri Suryawati (Berita Kedokteran Masyarakat (BKM), 2017)
Social support and medication obedience with recurrence of schizophrenia patients in PurworejoPurposeThe purpose of this paper was to determine the relationship of social support and medication obedience with recurrence of post-hospitalized schizophrenia patients.MethodsA cross-sectional study was conducted in November-December 2016 involving 126 schizophrenic patients at Tjitrowardojo General Hospital with patients meeting the inclusion and exclusion criteria.ResultsThe recurrence of schizophrenic patients relates to the amount of information support, instrumental support satisfaction and medication obedience, education.ConclusionThis study contributes to the knowledge that social support and medication obedience have an effect on the recurrence of schizophrenic patients. This study suggests health workers to educate the public about the impact of recurrence, the importance of medication and social support for schizophrenic patients.